2006
DOI: 10.1002/jms.1095
|View full text |Cite
|
Sign up to set email alerts
|

Laser desorption/ionization techniques in the characterization of high molecular weight oil fractions. Part 1: asphaltenes

Abstract: The molecular weight distribution of the asphaltene fractions of two types of crude oils from two different Italian fields (samples 1 and 2) was investigated. The analytical tools used to perform these analyses were matrix assisted laser desorption ionization (MALDI) and laser desorption ionization (LDI) mass spectrometry. After observing that the use of the matrix (as well as the addition of Ag+) did not improve the quality of the data compared to that obtained in LDI conditions, all further measurements were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
47
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 23 publications
8
47
0
Order By: Relevance
“…Using APPI ionization, the fragmentation is largely reduced and, therefore, the masses detected should be more representative of the true MW of the sample. The mass range found, between m=z 250-1100 with a maximum at m=z 500-600, is in very good agreement with previous works (Hortal et al, 2007;Merdrignac, 2007;Rizzi et al, 2006), whereas the eventual presence of higher masses (>100,000 u), as found by other authors (Islas et al, 2003;Karaka et al, 2004), cannot be investigated because the mass limit of the ion trap mass spectrometer is about 3000-4000 u for single-ionized analytes.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Using APPI ionization, the fragmentation is largely reduced and, therefore, the masses detected should be more representative of the true MW of the sample. The mass range found, between m=z 250-1100 with a maximum at m=z 500-600, is in very good agreement with previous works (Hortal et al, 2007;Merdrignac, 2007;Rizzi et al, 2006), whereas the eventual presence of higher masses (>100,000 u), as found by other authors (Islas et al, 2003;Karaka et al, 2004), cannot be investigated because the mass limit of the ion trap mass spectrometer is about 3000-4000 u for single-ionized analytes.…”
supporting
confidence: 88%
“…It can be assumed that the low resolution is due to the simultaneous desorption and ionization of many species with very small mass differences that cannot be resolved by the time of flight (TOF) analyzer. The complexity of the spectrum can be also due to the occurrence of in-source fragmentations originating either from photon irradiation or thermal effects (Rizzi et al, 2006). Some authors suggested the necessity of using a matrix to generate ions from the larger mass materials of asphaltenes (Herod et al, 2008).…”
Section: Mass Spectrometry Of Large Aromatic Molecules 643mentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the matrix is to absorb UV laser radiation and to energize the analyte (often not in the absorbing UV region), in order to ionize it more gradually (Pash et al, 2003;Watson and Sparkman, 2007). However, many polycondensed systems, especially those with aromatic moieties and, therefore, strong UV absorption, have the so-called "self-matrix" property (Apicella et al, 2007;Rizzi et al, 2006), which indicates the capability of the sample (or a part of it) to act as a matrix by itself. In this case, direct photoionization takes place by laser irradiation without the necessity of an external matrix addition (Apicella et al, 2010).…”
Section: Influence Matrixmentioning
confidence: 99%
“…MALDI became an established mass spectrometry method for macromolecular compounds. LDI/MALDI coupled to time of flight mass spectrometry (TOF) has been applied in petroleomics for the characterization of petroporphyrins [12], crude oils [13], and their fractions [14,15], in addition to the determination of the molecular-weight distributions (MWDs) of asphaltenes [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%